Caribbean Report 21-02-1990 - Fraser, Sonia (anchor); Markowitz, Arnold (correspondent); Robinson, A.N.R. (interviewee); Buxton, Neil (analyst); Norton, Michael (correspondent); Honeyghan, Lloyd (interviewee); Dark, Ian (correspondent) (The British Broadcasting Corporation, 1990)
The program reports on the address of A.N.R. Robinson, Prime Minister of Trinidad and Tobago at the United Nations Special Assembly on Drugs. The proposal issued by Trinidad and Tobago includes the setting up of an International Criminal Court and an International Tribunal. Secondly, the nineteen year old brother of Bob Marley, Anthony Booker is shot dead in Miami after rampaging through a shopping precinct with a firearm. Following the Financial News, Haiti moves nearer to the start of the electoral timetable and a census is due to start in March. One of the members of the electoral council which drafted the electoral schedule is calling for it to be revised. The report also covers the return of three exiled opposition leaders to Haiti. The final segment explores the upcoming WBA Welter Weight Title between Lloyd Honeyghan and Mark Breland.
1. Headlines (00:00-01:30)
2. Trinidad and Tobago addresses the United Nations Special Assembly on Drugs. Interview with A.N.R. Robinson, Prime Minister of Trinidad and Tobago (01:31-05:25)
3. Bob Marley's brother shot dead after rampage at a Miami shopping precinct. Arnold Markowitz, Miami Herald reports (05:26-09:00)
4. Financial News. Neil Buxton of Shearson Lehman Co., comments on the rising price of gold (09:01-10:30)
Keywords: Drug control.; International criminal courts.; Marley, Bob -- Family.; Elections -- Haiti.; Politicians -- Haiti -- Expulsion.; Boxing matches.; United Nations Special Assemble on Drugs.; Booker, Anthony.